Pruning Blueberry Plants in Florida - Jeffrey G. Williamson; Frederick S. Davies; Paul M. Lyrene (EDIS)
Pruning has long been recognized as a beneficial cultural practice in blueberry growing. Skillful pruning requires experience and growers generally develop their own style which may be slightly different from their neighbor's, but should accomplish the same objectives. This document discusses some basic principles of pruning and provides a few suggestions and observations which may be helpful in determining how and when to prune blueberries in Florida. This document is HS985, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2004.